Epistemologi Ilmu Dalam Perspektif Filsafat Isyraqi (Suhrawardi al-Maqtul) - Zikri Adib Kurnia; Ahmad Fajar Shodiq; Imron Rossidy (PT. ALHAFI BERKAH INDONESIA, 2024)
Isyraqi or in philosophical language illuminationism is a thought developed by Suhrawardi Al Maqtul by combining the teachings of Sufism and philosophy. Epistemologically, Islamic thought was born as a reaction or alternative to the weaknesses that occurred in previous philosophy, especially Aristotelian paripathetics. There are two main teachings in Isyraqi philosophy, namely gradations of essence and self-awareness. From these two teachings, a third teaching or theory was born, namely the Mythical Realm. The israqi philosophical view regarding methods of gaining knowledge emphasizes the importance of enlightenment or